Morphology and Wettability of [Bmim] [PF6] Ionic Liquid on HOPG Substrate - 张福春 沙茂林 任秀平 吴国忠 胡钧 张益 (Chinese physics letters, 2010)
We investigate the morphology and wettability of [Bmira][PF6] ionic liquid （IL） on a highly oriented pyrolitic graphite （HOPG） substrate using atomic force microscopy. Thin films, nanometer-sized droplets, and ＂drop-onlayer＂ structures of the IL are found on the substrate. Films with a thickness of up to 2nm （about 4 IL layers） show the solid-like behavior. In contrast, a dewetting phenomenon is observed for thicker IL films, indicating that the IL films retain liquid properties. The contact angle of a buck IL droplet on the HOPG is measured to be about 35°. The wettability of the bulk IL droplet on the HOPG is found to be quite different from that of IL films. These results indicate that the IL molecules can be organized into various micro-morphologies when they are confined to a solid substrate and show characteristic behavior at nanometer scales.